Peran Etika Bisnis dalam Membangun Budaya Kerja yang Bertanggung Jawab - Deva Jakaria Sinaga; Fiesto De Limawan; Francois Louis; Susan Grace Nainggolan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the role of business ethics in building a responsible work culture at PT. Sinergi Karsa Utama (PT. SKU). A qualitative case study approach was used, involving in-depth interviews with leaders and key employees, as well as participant observation. The results indicate that business ethics serves as a